Hydrological change in southern Australia over 1750 years: a bivalve oxygen isotope record from the Coorong Lagoon - B. K. Chamberlayne; J. J. Tyler; D. Haynes; D. Haynes; Y. Shao; J. Tibby; B. M. Gillanders (Climate of the Past, 2023)
Multi-centennial records of past hydroclimate change are essential for understanding the resilience of ecosystems to climatic events in addition to guiding conservation and restoration efforts. Such data are also crucial for examining the long-term controls over regional hydroclimate and the inherent variability in extreme droughts and floods. Here, we present a 1750-year record of hydroclimate variability in the Coorong South Lagoon, South Australia, part of an internationally significant wetland system at the mouth of Australia's largest river, the Murray River. Oxygen isotope ratios were measured from Arthritica helmsi bivalve shells preserved in sediments. The oxygen isotope record shows periods of persistent low and high moisture balance, from ∼500 to 1050 years and from ∼1300 to 1800 years, respectively, which is consistent with other hydroclimate reconstructions from the region. The range of oxygen isotope values in the sedimentary shells does not differ significantly from the estimated range of modern specimens from the present-day lagoon. These data suggest that the restricted and highly evaporated modern-day conditions are not markedly different to the pre-impacted state over the last 1750 years, although the absence of A. helmsi in the contemporary lagoon is likely a response to increased salinity, nutrient loading, and anoxia during the last century. These insights are potentially useful both in guiding management efforts to conserve and restore the Coorong Lagoon and for understanding long-term water resource availability in the region.